Retorik Pengucapan Dakwah Ustaz Ismail Kamus - Siren, Nor Raudah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2000)
This article discusses an effective style of speech in da'wah in reference to the rhetorical speech of Dato' Ismail Kamus. The article also discusses a discipline of rhetorical theory applied in an effective da'wah such as ethos, pathos and logos.